2017
DOI: 10.1039/c6ra28061g
|View full text |Cite
|
Sign up to set email alerts
|

C-7 modified flavonoids as novel tyrosyl-tRNA synthetase inhibitors

Abstract: Twenty C-7 modified flavonoids were designed and synthesized. Biological evaluation in vitro indicated that compounds generated by SYBYL-X with high scores also showed good inhibitory activities against TyrRS.Compounds containing the nargenin core exhibit better enzyme inhibitory activities than other flavonoid cores, with (S)-5-hydroxy-4 0 -hydroxy-7-(2-morpholino-2-oxoethoxy)-2,3-dihydroflavone (b1) being the most active (IC 50 ¼ 0.10 AE 0.01 mM) in all assayed compounds. All compounds were also assayed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…aureus (sixfold more potent than the marketed antibiotic ciprofloxacin). The result showed that R4 (N‐containing heterocyclic compounds) were more active than alkyl or aromatic amino containing analogues at the C‐7 side chain (Xiao et al, )…”
Section: Synthetic Derivatives Of Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus (sixfold more potent than the marketed antibiotic ciprofloxacin). The result showed that R4 (N‐containing heterocyclic compounds) were more active than alkyl or aromatic amino containing analogues at the C‐7 side chain (Xiao et al, )…”
Section: Synthetic Derivatives Of Flavonoidsmentioning
confidence: 99%
“…coli , and this compound indicated complete inhibition of FabI activity at the concentration of 100 μM (Allison et al, ). In 2017, the enzyme assays of 20 C‐7 modified flavonoids for inhibition tyrosyl‐tRNA synthetase in Gram‐positive and Gram‐negative organism revealed that ( S )‐5‐hydroxy‐40‐hydroxy‐7‐(2‐morpholino‐2‐oxoethoxy)‐2,3‐dihydroflavone ( 160 ) exhibited better activity against Gram‐negative organism with IC 50 lower than 1 mM (Xiao et al, ).…”
Section: Mechanism Of Antibacterial Activitymentioning
confidence: 99%
“…Flavones form a complex with cell wall components and consequently inhibit further adhesions and microbial growth as well. The inhibition of bacterial enzymes (such as tyrosyl-tRNA synthetase) was observed for C-7-modified flavonoids containing the naringenin (81) core [ 147 ]. It was also demonstrated that they were also inhibitors of S. aureus , E. coli , and Pseudomonas aeruginosa growth.…”
Section: Mechanism Of Antibacterial Activity Of Polyphenolsmentioning
confidence: 99%
“…S1(b) in ESI, † aer 8 hours of standing, Gr sheets aggregate partly in NMP, but, Gr-PANI 10:1 composite ller shows excellent dispersibility due to the p-p non-covalent interactions between Gr and PANI, indicating that the PANI can avoid the agglomeration of Gr sheets in the organic solvent. 18 The SEM morphologies of Gr, Gr-PANI 10:1 , PI and 40%Gr-PANI 10:1 @PI are shown in Fig. 2.…”
Section: Characteristics and Morphologymentioning
confidence: 99%